Genetic progress achieved over ninety-three years of sunflower breeding in Argentina, 1931–2024 - De la Vega, Abelardo J.; Zuil, Sebastian; Vázquez, Arnaldo N.; Bertero de Romano, Amelia (Elsevier, 2025)
Context: Genetic gain studies addressing parts of the history of sunflower breeding in Argentina (1931–2024) have been published, but many gaps remain. Objective: To fill all gaps in the quantification of sunflower genetic progress in Argentina. Methods: A multi-environment dataset of 1074 field trials (1935–2023) was analyzed using linear models, regression, and self-organizing maps (SOM) in the context provided by historical production periods. Results: Open pollinated variety (OPV) breeding (1938–1990) did not produce significant yield progress but shortened maturity, increased oil concentration, improved agronomics and contributed to building a locally adapted genetic pool. Hybrids that replaced OPVs (1970–1990) showed earlier maturity and higher values for oil yield and its immediate determinants. Genetic gains estimated for the period 1953–2022 were −0.15 % yr−1, 0.72 % yr−1, 0.46 % yr−1 and 1.49 % yr−1 for time to flowering, grain yield, oil concentration and oil yield, respectively. A slowdown in genetic progress was observed starting in the mid-1990s, associated with crop displacement, pathogen and pest evolution, and linkage drag shown by early herbicide-resistant hybrids. Conclusions: Sunflower breeding programs of Argentina consistently released superior genotypes at rates of genetic gain that are comparable to larger, better resourced crop growing systems.